2017
DOI: 10.1007/s00787-017-1088-6
|View full text |Cite
|
Sign up to set email alerts
|

Living with conduct problem youth: family functioning and parental perceptions of their child

Abstract: Parenting children with conduct problems (CP) is challenging, yet very little is known about the impact of the child’s behaviour on family functioning or how parents of children with CP perceive their child. The aim of this research was to examine whether families with children with CP and high vs. low levels of callous–unemotional traits (HCU vs. LCU) experience differences in family functioning and parental perceptions. One hundred and one parents/caregivers of boys aged 11–16 [Typically developing (TD) n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…Conflicts between family members were also addressed in previous studies. [ 14 ] Marital infidelity is another frequent problem in these families. It seems that families with parents who have extramarital relationships are more susceptible to raising children with disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicts between family members were also addressed in previous studies. [ 14 ] Marital infidelity is another frequent problem in these families. It seems that families with parents who have extramarital relationships are more susceptible to raising children with disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six boys met CP/LCU criteria with ICU scores less than or equal to 42 and twenty-eight boys met criteria for CP/HCU with ICU scores greater than 42. Other studies employing the median split approach to assign boys with conduct problems into CP/HCU and CP/LCU groups have reported median scores of the ICU ranging from 30 to 42 (Hodsoll et al 2014 ; Jones et al 2010 ; Martin-Key et al 2017 ; O’Nions et al 2017 ; Roberts et al 2018 ; Schwenck et al 2012 ; Sebastian et al 2016 ; Sethi et al 2018 ) and a recent study has suggested that a score of 41 may represent a clinically meaningful cut-off for HCU (Docherty et al 2017 ). The median split of 42 in the current study is thus higher than or comparable to median split scores in previous research and designates a group of children with extreme CU scores within clinically significant range (estimated to be within the top 5% of the population).…”
Section: Methodsmentioning
confidence: 99%
“…Conduct problems refer to antisocial behaviors displayed in childhood and/or adolescence that are symptomatic of conduct disorder and oppositional defiant disorder [ 1 ]. They account for a substantial proportion of personal [ 2 ], familial [ 3 ], and societal burden [ 4 6 ], and are associated with negative outcomes across multiple domains, including mental and physical health problems [ 7 , 8 ]. It is therefore crucial to thoroughly understand the etiology of such difficulties and to develop effective prevention and intervention programs.…”
Section: Introductionmentioning
confidence: 99%